LIMONENE IN SCHOOL INDOOR ENVIRONMENTS – SOURCE AND LEVEL OF CONTAMINATION - BLAGA, Andrea Brigita; DUMITRAȘCU, Irina; BRAD, Andreea (Studia Universitatis Babeș-Bolyai Ambientum, 2015)
Little information currently exists regarding indoor air pollution with limonene in school environments. This study’s aim is to assess the contamination level of limonene and identify possible emission sources inside classrooms because, it is well known that exposure to higher levels of monoterpenes may have important human health effects, children being more susceptible than adults. A field study was conducted in two classrooms from different schools in Alba County, Romania by tracing the evolution of the pollutant over one school day (inside and outside simultaneously) and filling up a specific check-list. Indoor limonene levels ranged between 0.064 – 0.236 mg/m3 for school ro-s1 and 0.022 – 0.164 mg/m3 for ro-s2 school, exceeding in both cases outdoor levels, therefore concluding that indoor sources have been prevalent. Among them, laminate floorings, wooden construction materials, furniture, cleaning agents and living plants have been identified as common for both classrooms. Outdoor air quality didn’t have an important effect over the indoor environment, poor ventilation determining the low influence of outdoor concentration levels.